The Impact of Serial Cyclone Clustering on Extremely High Sea Levels in the Baltic Sea - Mika Rantanen; Daan van denBroek; Joona Cornér; Victoria A. Sinclair; Milla M. Johansson; Jani Särkkä; Terhi K. Laurila; Kirsti Jylhä (Geophysical Research Letters)
Abstract In the Baltic Sea, sea level variations are often very pronounced. During the winter season, storm surges caused by strong extratropical cyclones (ETCs) can have major societal impacts on coastal cities. In this study, using reanalysis‐based cyclone tracks and in‐situ tide gauge records, we show that serial cyclone clustering (SCC) leads to higher sea levels in the Baltic Sea than situations where only one ETC passes the tide gauge. Consequently, almost half of extreme sea level events in the Baltic Sea are associated with cyclone clustering periods. For example, in Helsinki, 45% of the extreme sea level events coincided with SCC periods of three or more ETCs, while only 6% of the events coincided with a single ETC. Our study represents a significant advance in the understanding of the factors influencing sea level variations in the Baltic Sea.